PERLAWANAN EKSTRA LEGAL: “TRANSFORMASI PERLAWANAN PETANI MENGHADAPI KORPORASI PERKEBUNAN” - Muhammad Afandi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2013)
History of plantation is the history of peasants’ land grabbing in Nusantara. The peasants have responded thissituation with resistance in many ways. The theme of the research is peasant resistance during the transition of democracyorganized by peasant movement of Deli Serdang confronts PTPN II. This research reveals that the peasants consider thatreformation era has opened political chance for them to struggle in legal ways. But when the resistance in legal way is deadlocked, the peasants took another way to rebel, in the extra legal way, with its consequences such as open war with nationalmilitary or civilian militia recruited by PTPN II. The birth of extra legal movement is the consequence of nation failure and it isalso the consequence of the contradictions of the formal law in handling agrarian conflict.Keywords: PTPN II, peasant social movement, reclaiming, rebellion transformation.